Developing a methodology for estimating the drag in front-crawl swimming at various velocities - Narita, K.; Nakashima, M.; Takagi, H. (Journal of Biomechanics, 2017)
We aimed to develop a new method for evaluating the drag in front-crawl swimming at various velocities and at full stroke. In this study, we introduce the basic principle and apparatus for the new method, which estimates the drag in swimming using measured values of residual thrust (MRT). Furthermore, we applied the MRT to evaluate the active drag (Da) and compared it with the passive drag (Dp) measured for the same swimmers. Da was estimated in five-stages for velocities ranging from 1.0 to 1.4 m s-1; Dp was measured at flow velocities ranging from 0.9 to 1.5 m s-1 at intervals of 0.1 m s-1. The variability in the values of Da at MRT was also investigated for two swimmers. According to the results, Da (Da = 32.3 v3.3, N = 30, R2 = 0.90) was larger than Dp (Dp = 23.5 v2.0, N = 42, R2 = 0.89) and the variability in Da for the two swimmers was 6.5% and 3.0%. MRT can be used to evaluate Da at various velocities and is special in that it can be applied to various swimming styles. Therefore, the evaluation of drag in swimming using MRT is expected to play a role in establishing the fundamental data for swimming.